Natural history and screening of interstitial lung disease in systemic autoimmune rheumatic disorders. (August 2021) - Panagopoulos, Panagiotis; Goules, Andreas; Hoffmann-Vold, Anna Maria; Matteson, Eric L.; Tzioufas, Athanasios
Interstitial lung disease (ILD) is a relatively frequent manifestation of systemic autoimmune rheumatic disorders (SARDs), including systemic sclerosis (SSc), rheumatoid arthritis (RA), idiopathic inflammatory myopathies (IIM), systemic lupus erythematosus (SLE), primary Sjögren's syndrome (pSS), and anti-neutrophil cytoplasmic antibody (ANCA) associated vasculitis. Interstitial pneumonia with autoimmune features (IPAF) has been proposed to describe patients with ILD who have clinical or serological findings compatible with SARDs but they are not sufficient for a definite diagnosis. ILD may present with different patterns among patients with SARDs, but most commonly as nonspecific interstitial pneumonia (NSIP), with the exception of RA and ANCA vasculitis that more often present with usual interstitial pneumonia (UIP). The natural history of ILD is quite variable, even among patients with the same SARD. It may present with subclinical features following a slow progressively course or with acute manifestations and clinically significant rapid progression leading to severe deterioration of pulmonary function and respiratory failure. The radiographic pattern of ILD, the extent of the disease, the baseline pulmonary function, the pulmonary function deterioration rate over time and clinical variables related to the primary SARD, such as age, sex and the clinical phenotype, are considered prognostic factors for SARDs-ILD associated with adverse outcomes and increased mortality. Different modalities can be employed for ILD detection including clinical evaluation, pulmonary function tests, high resolution computed tomography and novel techniques such as lung ultrasound and serum biomarkers. ILD may determine the clinical outcome of SARDs, since it is associated with significant morbidity and mortality and therefore screening of patients with SARDs for ILD is of great clinical importance.